Laparoscopic surgery versus robot-assisted surgery for choledochal cyst excision: A systematic review and meta-analysis - Zhang, Ke; Zhao, Difang; Xie, Xiaolong; Wang, Wentao; Xiang, Bo (Frontiers in Pediatrics, 2022)
The aim of this following study is to systematically review and analyze the published data comparing laparoscopic surgery and robotic assisted surgery for choledochal cyst excisions through the metrics of operative time, length of hospital stay and postoperative outcome. PubMed, Web of Science, Embase, Ovid, and the Cochrane Library databases were combed through and data was retrieved from the timespan between January 1995 and October 2021. The primary measures included operative time, intraoperative bleeding, hospital stay, and postoperative complications. Quality and risk of bias were assessed using the Newcastle-Ottawa Quality Assessment Scale. Making use of random-effects models, we pooled the odds ratios (ORs) and mean differences (MDs) with 95% confidence intervals (95% CIs). Six studies comprising a total 484 patients who had undergone either laparoscopic surgery [307 (63.43%) patients] or robot-assisted surgery [177 (36.57%) patients] were included in this analysis. Three of the articles involved adults while the other three involved children. All of the studies were published after 2018 and were retrospective case–control studies. Patients undergoing robotic surgery had a shorter hospital stay (MD, 0.95; 95% CI, 0.56 to 1.35; p < 0.00001) and a longer operative time (MD, −57.52; 95% CI, −67.17 to −47.87; p < 0.00001). And there was no significant discrepancy in complications between the two groups. Compared to laparoscopic surgery, robot-assisted surgery is associated with a shorter hospital stay, scores highly in terms of both safety and feasibility, however it also results in a longer operative time. And the two procedures have the same short- and long-term results.